Knowledge and practices of primary care givers regarding care of diabetics at home - Nyirenda, Wakhonderachi Temweka (Kamuzu University of Health Sciences, 2022)
This study is about knowledge and practices of primary care givers in regards to care of diabetics at home. The objectives of the study are to: Assess the level of knowledge of primary care givers on care of diabetic clients at home, Identify the type of care given by the primary care givers at home, explore perceptions of primary care givers on care of diabetics at home and explore challenges faced by primary care when providing care to diabetics. The study will be qualitative in nature. In depth interviews using an interview guide will be conducted on 15 primary care givers who will escort their diabetes clients at Kamuzu Central Hospital (K. C.H.) diabetes clinic. Before data collection, a pilot study will be conducted at Queen Elizabeth central hospital (Q. E. C .H) diabetes clinic. Data will be analysed manually and category scheme will be used to come up with the main themes from the primary care givers knowledge and practices. Ethical considerations will be adhered to in order to ensure fair treatment of participants and also to avoid any form of harm to the participants.